2018
DOI: 10.1080/14670100.2018.1509531
|View full text |Cite
|
Sign up to set email alerts
|

Protecting against electrode insertion trauma using dexamethasone

Abstract: Dexamethasone-eluting intra-cochlear arrays may inhibit osteoneogenesis, and reduce spiral ganglion neuron loss following traumatic cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Many experimental studies in animals have demonstrated that the use of corticosteroids is able to preserve hearing thresholds, increase the survival of hair cells and spiral ganglia, and decrease the formation of new fibrotic tissue within implanted cochlea (20)(21)(22)(23)(24)(25)(26)(27). Clinical studies demonstrate lower impedances and improved preservation of low-frequency residual hearing in patients when corticosteroids are used in CI surgery (28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many experimental studies in animals have demonstrated that the use of corticosteroids is able to preserve hearing thresholds, increase the survival of hair cells and spiral ganglia, and decrease the formation of new fibrotic tissue within implanted cochlea (20)(21)(22)(23)(24)(25)(26)(27). Clinical studies demonstrate lower impedances and improved preservation of low-frequency residual hearing in patients when corticosteroids are used in CI surgery (28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Data from two published animal studies favor the local application of glucocorticoids over systemic application in order to minimize the consequences of insertion trauma (26,27). On the contrary, results of another study showed better hair cell protection after local application but a more robust prevention of fibrosis for systemic administration (37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work by Chambers et al demonstrated greater hearing threshold shifts in implantation models eliciting more mechanical trauma regardless of DEX [32]. This study examined the benefit of DEX in two implant models: a low trauma model where an electrode array was carefully introduced into the cochlea, and a high trauma model where a steel wire was inserted and withdrawn twice prior to insertion of the electrode array.…”
Section: Drug-eluting Electrodementioning
confidence: 99%
“…Sustained concentrations of about 60 and 100 ng/mL were observed in the perilymph for the 1 and 10% loaded rods respectively, demonstrating the potential for therapeutic dosing by loading of DEX into the silicone of a CI electrode array. Commercial arrays with silicone loaded with 40% (w/w) DEX demonstrated inhibition of osteoneogenesis and reduced SGN loss four weeks postimplant in a guinea pig model of high insertion trauma [33]. Briggs and colleagues demonstrated a first-time-in-human study of a DEX-eluting investigational electrode array [34**].…”
Section: Steroid Elution Coatingsmentioning
confidence: 99%